How the war economy centred in the eastern region of the Democratic Republic of the Congo is fuelling the conflict in the Great Lakes Region (1998-2016) - Mokose, Manapo Tebello; Solomon, Hussein (University of the Free State, 2016)
Millions have been killed in the eastern Democratic Republic of the Congo (DRC). Despite various mediation efforts and having one of the largest United Nations/ African Union peacekeeping forces in the world, the carnage continues to claim more victims. What this paper argues is that the underlying war economy must be seen as the basis of the ongoing violence and only its eradication and replacement by a peace economy will there be any hope for sustainable peace both in the DRC and the broader Great Lakes Region. To this end, the paper provides a historical background to the conflict, and then proceeds to contextualize this economy within the war and peace economy literature. The intricacies in the war economy are then unravelled followed by certain policy recommendations to end the violence.
Keywords: Democratic Republic of the Congo (DRC); Great Lakes Region; Nations/ African Union peacekeeping forces; War economy; Peace economy; Conflict; Violence